Investigation of the Effects of Splenectomy on Bone Healing (Experimental Study) - Gultekin, Muhammet Zeki; Yuksel, Serdar; Alagoz, Ender; Ozsoy, Sule; Avci, Ali; Gulec, Mehmet Akif; Bayramoglu, Zeynep (ISTANBUL TRAINING & RESEARCH HOSPITAL, 2021)
Introduction: This study is an experimental setup to examine the effects of splenectomy, applied to multi-trauma patients who are commonly seen in emergency traumatology practices and on fracture healing processes with respect to histopathological, biomechanical, and radiological aspects. Methods: Further, 32 male Sprague Dawley rats (10 months old; average weight 394.5 +/- 28.3 g) are included in the study. In a dark environment, rats are fed at 22 degrees C for 12 hours with standard rodent food ad libitum. They are divided into two groups: splenectomy (total splenectomy and long bone fracture healing) and control (only long bone fracture healing n=16). Four months after surgery, rats are killed, and callus tissues in fractured femurs were examined histopathologically, radiologically, and biomechanically. Results: In the radiological analysis of the femur materials in relation to the case and control groups, there was no substantial difference in the Goldberg classification score (p>0.05). Similarly, no substantial difference was observed (p>0.05) in histopathological examinations and biomechanical analysis conducted in femur samples. Conclusion: When all of the results obtained in our study are evaluated together, it was concluded in the rats to which splenectomy is applied that this did not affect fracture healing histopathologically, biomechanically, and radiologically, despite the modification of immune modulators.
Keywords: Bone healing; splenectomy; immune; FRACTURE; EXPRESSION; SPLEEN; RATS; General & Internal Medicine